The effectiveness of Central Bank intervention: evidence from Turkey - Tuna, Gulcay (Routledge Journals, Taylor & Francis Ltd, 2011)
This article investigates the effectiveness of Central Bank intervention on the conditional variance and the mean of the exchange rate returns in Turkey during the float period. The daily exchange rates are studied within an Exponential General Autoregressive Conditional Heteroskedastic (EGARCH) framework. Little evidence is found for the effectiveness of intervention operations. Empirical results suggest that foreign exchange (FX) selling auctions increase exchange rate volatility. However, a reverse causality relationship detected between one-day past sales of FX auctions and exchange rate returns which is supportive of leaning-against-the-wind behaviour of the Central Bank contradicts its announcements. Also the Central Bank of Turkey (CBT) tends to intervene through FX selling auctions when one-day past volatility is higher.
Keywords: Foreign-Exchange Rates; Conditional Heteroskedasticity; Rate Volatility; Heteroscedasticity; Variance; Model